Reflection of Strategic Thinking on the Organizational Change - Firas Mohammed, Ismael (Opción, 2019)
The purpose of this research is to determine the relationship between the strategic thinking and organizational change via the use of many statistical methods such as Simple linear regression equation. The 80% of the hypotheses of correlation and influence were established, and the research was reached a number of conclusions. Including the fluctuation of the level of strategic thinking capabilities in the sample surveyed. Although, there are certain levels, but an organization of this importance need to be higher. Based on these conclusions, the researcher has made some recommendations to address the findings of the research.